Analytical Analysis Of Implementation Issues And Its Practical Applicability In DVB-NGH Single Frequency Networks (International Journal of Engineering and Computer Science, 2015)
The role of the television has huge impact on the 21st century and basically the televisions either make use of SFN single frequency networks (SFN) or multi frequency networks (MFN) and both these networks are ideal for meeting the practical requirements either in local and global services. Another important drawback in these two networks are these two networks consumes huge amount of spectrum. The single frequency networks (SFN) main approach is it radiates the same amount of signal both in terms of time and frequency and Without violating the SFN principle, local services meant to address sub-regions of an SFN must therefore be transmitted throughout the whole network, causing inefficient distribution of local services. A novel approach has been proposed in this paper where high equipped next generation mobile broadcasting standard digital video broadcasting—next generation handheld for providing global and local contents in SFN topologies: hierarchical modulation (H-LSI) and orthogonal local services insertion (O-LSI) techniques. H-LSI uses hierarchical modulation to transmit local services on top of the global services in areas close to the transmitters, by transmitting the local services in the low priority stream and the global services in the high priority stream. The O-LSI scheme specifies groups of OFDM subcarriers in specific OFDM symbols for the exclusive use of particular transmitters to transmit local services. For both techniques, the transmission of local content through the whole SFN network can be scheduled in a way that different local areas do not interfere with each other. In addition to the description of both H-LSI and O-LSI schemes, the applicability of these approaches in terms of network topologies, implementation issues, and performance evaluation are analyzed.